2010
DOI: 10.1111/j.1464-410x.2009.09073.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular morbidity, heart rates and use of antimuscarinics in patients with overactive bladder

Abstract: bladder dysfunction, nor a pharmacy claim for antimuscarinics, formed the non-OAB cohort. CV comorbidities and use of medications with antimuscarinic effects were assessed for the 12 months before OAB diagnosis/treatment. Information on heart rate (HR) on the day of the first OAB drug prescription was obtained from the GE Healthcare dataset. HR was assessed for patients aged ≥ 18 years with a diagnosis of OAB who were prescribed antimuscarinics (oxybutynin or tolterodine) at any dose or oral formulation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 32 publications
4
49
1
2
Order By: Relevance
“…This might be especially important considering that the incidence of OAB, and subsequently the incidence of antimuscarinic drug treatment, also increase with age [4,5]. Together, these conditions and the well-established relationships between age, increasing HR, and mortality/morbidity rates can make patients with OAB and concomitant cardiovascular diseases more vulnerable to the cardiac side-effects of antimuscarinics [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be especially important considering that the incidence of OAB, and subsequently the incidence of antimuscarinic drug treatment, also increase with age [4,5]. Together, these conditions and the well-established relationships between age, increasing HR, and mortality/morbidity rates can make patients with OAB and concomitant cardiovascular diseases more vulnerable to the cardiac side-effects of antimuscarinics [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study showed that the prevalence of cardiovascular comorbidities is significantly higher in patients with than without OAB and that previous exposure to medications with antimuscarinic effects was also higher in patients with OAB [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Importantly, the various available antimuscarinics are metabolized differently, with some agents metabolized through the hepatic cytochrome P450 system. This is particularly important to be aware of for patients taking multiple medications, as many common drugs are also inducers, inhibitors or substrates of the various isoenzymes of this system.…”
Section: Considerations For Luts Pharmacotherapymentioning
confidence: 99%
“…Dieser Trend konnte auch in der Subanalyse einzelner kardiovaskulär bedingter Erkrankungen bestätigt werden. Im Rahmen dieser retrospektiven Studie untersuchten Andersson et al [1] ebenfalls die möglicherweise negativen Auswirkungen einer antimuskarinergen Therapie auf kardiovaskuläre Komorbiditäten. Sie Fazit.…”
Section: Risikofaktorenunclassified